Home of the brave - Applegate, Katherine (Feiwel And Friends, 2007)
Kek, an African refugee, is confronted by many strange things at the Minneapolis home of his aunt and cousin, as well as in his fifth-grade classroom, and longs for his missing mother, but finds comfort in the company of a cow and her owner.